2014
DOI: 10.1002/ar.23051
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin‐Mediated Endocytosis of Gold Nanoparticles In Vitro

Abstract: Gold nanoparticles (AuNPs) have potential biomedical and scientific applications. In this study, we evaluated the uptake and internalization of FBS-coated 20 nm AuNPs into lung fibroblasts and liver cells by different microscopy techniques. AuNP aggregates were observed inside MRC5 lung fibroblasts and Chang liver cells under light microscopy, especially after enhancement with automegallography. Clusters of AuNPs were observed to be adsorbed on the cell surface by scanning electron microscopy. Ultrathin sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…Data from other groups show that the uptake of nanoparticles can occur via caveolin- 34 or clathrin-mediated endocytosis. 35 These data are in line with the vesicular distribution pattern of the gold nanoparticles after internalization.…”
supporting
confidence: 82%
“…Data from other groups show that the uptake of nanoparticles can occur via caveolin- 34 or clathrin-mediated endocytosis. 35 These data are in line with the vesicular distribution pattern of the gold nanoparticles after internalization.…”
supporting
confidence: 82%
“…By geometrical means, it may concluded that ErbB receptor retrograde trafficking will be dependent on plasma membrane budding and cytosolic vesicle formation [37,58]. The required deterministic character of nucleograde trafficking requires the participation of cytoskeleton elements and networks and proteins mediating the mechanical contact between the vesicle and its transporter [85,113,114]. The findings and processes given in Figure 2 illustrate this situation for MCF-7 breast epithelial cells after stimulation by NRG-1 or attenuation by trastuzumab, as well as after DNA damage-inducing irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the geometrical pathway a vesicle follows across the cell, the functional environment changes and the vesicle content and size is also altered by fusion processes with other vesicles and by digestion [113]. …”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles can also be internalized via clathrin-mediated endocytosis instead of by passive uptake. For example, aggregates of fetal bovine serum (FBS)-coated gold nanoparticles adhered to the cell membrane, and they were then taken into the cell by clathrin-mediated endocytosis (Ng et al, 2014). In general, nanoparticles form into aggregates and/or agglomerates in culture medium and are internalized as aggregates into the cell.…”
Section: Introductionmentioning
confidence: 99%